Continuous Glucose Monitoring in the Patients with Diabetic Nephropathy - 王锋 程东生 汪年松 李文卉 包玉倩 周健 贾伟平 (Shanghai jiao tong da xue xue bao, 2011)
The aim of this study was to compare the difference of blood glucose （BG） fluctuation in the patients of type-2 diabetes mellitus （DM-2） with and without clinical diagnosed diabetic nephropathy （DN） by the continuous glucose monitoring system （CGMS）. Thirty DM-2 patients with clinical diagnosed DN and fifteen DM-2 patients without complication underwent continuous glucose monitoring for 3 days （72 h） by CGMS. The difference of daily glucose fluctuation in both groups was compared by the parameter of CGMS. The 24-h mean blood glucose （MBG）, minimal BG （MIN-BG）, area under curve of BG over 7.8 （AUC7.8）, percentage of time of BG over 7.8 （PT7.8）, area under curve of BG over 11.1 （AUC11.1）, percentage of time of BG over 11.1 （PT11.1）, as well as mean of daily difference （MODD） were significantly increased in the group of DN, compared with those in the group of DM-2 without complication （all statistic probability P 〈0.05）. No statistical significance of mean amplitude of glycaemic excursion （MAGE） was found. In the group of DN, MBG, standard deviation of blood glucose （SDBG）, large amplitude of glycaemic excursion （LAGE）, AUC7.8, PT7.8, AUC11.1, PT11.L MAGE and MODD were （10.7±1.9）mmol/L, （2.5±1.3）mmol/L, （9.24-3.9）mmol/L, 3.2±1.7, （81±18）%, 1.2±1.0, （42±24）%, （5.8＋2.5） mmol/L and （2.6±1.5） mmol/L, respectively. The study showed that the BG level of the patients with DN fluctuated throughout the day. MBG of the patients with DN was higher than that of the patients of DM-2 without complications, with the characteristics of long-lasting high BG period, dramatic instability during the day and especially high postprandial blood glucose. CGMS is a useful tool for physicians to know the details of the change of BG in the patients with DN.